Effect of Cultivated Pastures on Soil Bacterial Communities in the Karst Rocky Desertification Area - Song, Shuzhen; Xiong, Kangning; Chi, Yongkuan; He, Cheng; Fang, Jinzhong; He, Shuyu (Frontiers in Microbiology, 2022)
Vegetation restoration has the potential to restore and improve soil quality and soil microbial diversity in degraded areas, and it is of great significance for maintaining the stability of karst degraded ecosystems. Soil bacteria play an important role in regulating the process of vegetation restoration in karst ecosystems. However, the effects of vegetation restoration for different artificial grassland on soil bacterial communities in the karst rocky desertification regions remain unclear. In this study, a 10-year long-term experiment was carried out on three artificial grassland vegetation restoration, namely, the Dactylis glomerata grassland (DG), the Lolium perenne grassland (LP), and the Lolium perenne + Trifolium repens mixed grassland (LT), and the natural grassland (NG) was used as the control. Using 16S rDNA Illumina sequencing, combined with 6 soil indicators and data models, we explored the effects of vegetation restoration for different artificial grassland on soil properties and soil bacterial communities. The results showed that the vegetation restoration of artificial grassland can improve the soil nutrient content and soil microbial biomass compared with the vegetation restoration of natural grassland. Among the three vegetation restoration of artificial grassland, the effect of LT was better than that of the DG and the LP. The vegetation restoration of artificial grassland increased the relative abundance of Proteobacteria, but decreased the relative abundance of Acidobacteria. Different grassland vegetation restoration significantly changed soil bacterial structure, and pH and MBC significantly increased soil bacterial diversity. The bacterial community in the LT treatment was the most beneficial to soil restoration. Permutation Test analysis showed that pH and SOC were the main factors affecting soil bacterial community. FAPROTAX analysis showed that all three vegetation restoration of artificial grassland increased the relative abundance of nitrogen fixation, but decreased the relative abundance of chemoheterotrophy and aerobic chemoheterotrophy. The results showed that compared with the vegetation restoration of natural grassland, the artificial grassland vegetation restoration was more conducive to soil restoration, and the LT was the most effective measure to increase soil nutrients, improve soil bacterial communities and promote the restoration of degraded ecosystems in the karst rocky desertification areas.